Pethia aurea (Teleostei: Cyprinidae), a new species of barb from West Bengal, India, with redescription of P. gelius and P. canius - Knight, J. D. Marcus (Zootaxa, 2013)
Fishes currently assigned to Pethia gelius Hamilton from West Bengal are shown to belong to a closely-related group of three species: P. gelius, its erstwhile synonym P. canius Hamilton and a new species, P. aurea. The three species are distinguished from all other species of Pethia by having the lateral line incomplete, with 3–4 pored scales; 20–26 scales in lateral series on body; ½4–5/1/2–3½ scales in transverse line on body; 8–9 predorsal scales; barbels absent and by a unique colour pattern consisting of two or three black blotches on the body (which, however, fade on preservation), the first behind the opercle, the second beneath the origin of the dorsal fin, extending to the mid-lateral region, and the third above the origin of the anal fin. A black spot is also present at the base of the dorsal and anal fins. Additionally, P. gelius is distinguished by having the last unbranched dorsal-fin ray thick, straight, serrated, with 20–25 serrae on its posterior margin; a snout length of 6.1–8.4 % standard length (SL); a body depth of 32.6–37.7 % SL; and a dorsal-fin height of 19.4–22.8 % SL. Pethia canius is additionally distinguished by having a snout length of 8.9–11.8 % SL; a body depth of 28.1–32.2 % SL; and dorsal-fin height of 26.9–32.8 % SL. Pethia aurea, new species, is additionally distinguished from all its congeners by having ½5/1/3–3½ scales in transverse line on body; 9 pre-dorsal scales; and last unbranched dorsal-fin ray slender, serrated, with 19–22 serrae on posterior margin.